A Need Analysis in English for Business Material at Economic Faculty of Pandanaran University - Tiara Nove Ria; Djamaludin Malik (Universitas Islam Nahdlatul Ulama Jepara, 2020)
This article’s aim is to find out what students’ of Economic Faculty of Pandanaran University need in learning English for Business course to improve the materials design. Since in Indonesia there are so many companies have already engaged with overseas client or customer, they have already applied English as media for communication in their daily work. Then, for preparing the readiness of the graduates to work at such company, there is English for Business course that must be taken by the students of Economic Faculty. However, the materials which are taught to students, so far, do not meet the students’ interest and need. That is why this study conducted to put the students first in improving materials. This quantitative and qualitative study used Needs Analysis Theory. Questionnaire and interview were conducted to collect the data and get all information to improve the materials design of English for Business Course. The participants of this study were an English lecturer, two HRD of multinational company, and 50 students of Economic Faculty at Universitas Pandanaran. The result of this study showed several found of materials that can be taught. Furthermore, it can be implemented in English for Business teaching.